2007
DOI: 10.1007/s00268-007-9273-2
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Ultrasonography in the Detection of Clinically and Mammographically Occult Breast Cancer

Abstract: The use of high-resolution USG may lead to detection of a significant number of occult cancers that are no different in size from nonpalpable mammographically detected lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…With the recent advances in technology, US and MRI allow to delineate occult malignancy in women with dense breast tissue, especially in case of high risk patients (5,7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the recent advances in technology, US and MRI allow to delineate occult malignancy in women with dense breast tissue, especially in case of high risk patients (5,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…These limitations are partially solved by the full-field digital mammography (FFDM), with its improved dynamic range, tissue contrast and post-processing, and by the digital breast tomosynthesis (DBT), which partially addresses the two-dimensional breast representation of planar mammography (4). Dual-energy contrast enhanced digital mammography represents a novel technique and has a reported sensitivity of 93% versus 78% of conventional mammography alone (6).With the recent advances in technology, US and MRI allow to delineate occult malignancy in women with dense breast tissue, especially in case of high risk patients (5,7,8).Recently, nuclear medicine imaging technology has been introduced in the field of breast cancer with the development of positron emission tomography (PET), PET- …”
mentioning
confidence: 99%
“…Our results may be superior to those from other studies because previously reported results have indicated a 9-14% frequency of DCIS in the cancers detected by US screening. (9,32,39,40) Izumori et al (41) examined US findings and histological features of 47 DCIS cases diagnosed by US alone compared with 103 DCIS cases diagnosed by mammography or clinically. Most DCIS cases detected by US alone were localized, showed few extensive intraductal components, and were of low grade according to the Van Nuys classification.…”
Section: Discussionmentioning
confidence: 99%
“…L'imaging convenzionale, rappresentato dalla mammografi a e dall'ecografi a, consente di ottenere una precoce individuazione della patologia mammaria qualora eseguito mediante rigorosi criteri metodologici e corretta successione temporale [2]. L'esame mammografi co rappresenta l'indagine di prima istanza nella diagnosi precoce del carcinoma della mammella nelle donne di età al di sopra dei 35-40 anni, mentre l'ecografi a costituisce, ad oggi, un'importante tecnica complementare all'esame mammografi co in grado di incrementarne la sensibilità e la specifi cità [3,4] e dirimerne i dubbi diagnostici nei casi di mammelle a prevalente componente fi broghiandolare, come unica indagine in donne di giovane età e nella valutazione della natura solida o liquida di radiopacità nodulari evidenziate [2,5]. Tuttavia, i limiti intrinseci dell'ecografi a e la sua inferiore sensibilità rispetto all'indagine mammografi ca nell'individuare la presenza di lesioni mammarie sospette, anche in relazione alle caratteristiche strutturali della componente ghiandolare ed all'esperienza dell'operatore, non consentono di utilizzare tale metodica come unica tecnica per la diagnosi precoce della patologia mammaria [6][7][8][9].…”
Section: Introduzioneunclassified